ReverseDock: a web server for blind docking of a single ligand to multiple protein targets using AutoDock Vina - Krause, Fabian; Voigt, Karsten; Di Ventura, Barbara; Öztürk, Mehmet Ali (Frontiers in Molecular Biosciences, 2023)
Several platforms exist to perform molecular docking to computationally predict binders to a specific protein target from a library of ligands. The reverse, that is, docking a single ligand to various protein targets, can be currently done by very few web servers that limit the search to a small set of pre-selected human proteins. However, the possibility to in silico predict which targets a compound identified in a high-throughput drug screen bind to would help optimize and reduce costs of the experimental workflow needed to reveal the molecular mechanism of action of a ligand.Here we present ReverseDock, a blind docking web server based on AutoDock Vina specifically designed to allow users with no computational expertise to dock a ligand to 100 protein structures of choice. ReverseDock expands the number and type of proteins a ligand can be docked to, making the task of in silico docking of a ligand to entire families of proteins straightforward. We envision ReverseDock will support researchers by providing the possibility to apply inverse docking computations on a web browser. ReverseDock is available at: https://reversedock.biologie.unifreiburg.de/